Vocal tract changes caused by phonation into a tube: a case study using computer tomography and finite-element modeling - Vampola, Tomás; Laukkanen, Anne-Maria; Horácek, Jaromír; Svec, Jan G (The Journal of the Acoustical Society of America, 2011)
Phonation into a glass tube is a voice training and therapy method that leads to beneficial effects in voice production. It has not been known, however, what changes occur in the vocal tract during and after the phonation into a tube. This pilot study examined the vocal tract shape in a female subject before, during, and after phonation into a tube using computer tomography (CT). Three-dimensional finite-element models (FEMs) of the vocal tract were derived from the CT images and used to study changes in vocal tract input impedance. When phonating on vowel [a:] the data showed tightened velopharyngeal closure and enlarged cross-sectional areas of the oropharyngeal and oral cavities during and after the tube-phonation. FEM calculations revealed an increased input inertance of the vocal tract and an increased acoustic energy radiated out of the vocal tract after the tube-phonation. The results indicate that the phonation into a tube causes changes in the vocal tract which remain also when the tube is removed. These effects may help improving voice production in patients and voice professionals.
Keywords: biologické modely; hlasové řasy; Female; zobrazování trojrozměrné; Imaging, Three-Dimensional; ženské pohlaví; Tomography, X-Ray Computed; rentgenový obraz - interpretace počítačová; Finite Element Analysis; lidé; Models, Biological; Pilot Projects; larynx; Vocal Cords; pilotní projekty; Speech Acoustics; Radiographic Image Interpretation, Computer-Assisted; Larynx; Phonation; akustika řeči; počítačová rentgenová tomografie; analýza metodou konečných prvků; lidé středního věku; fonace; Voice Quality; kvalita hlasu; Middle Aged; Humans